Wireless decode-and-forward relay channels: time allocation strategies for cooperation and optimum operation - Elsheikh, Elsheikh Mohamed Ahmed (LAP LAMBERT Academic Publishing, 2010)
Relay channels have been in use for decades as an effective means to tackle some of the challenges facing wireless transmission. Recent studies considered re-employing the relay channel to serve modern wireless systems. Material offered in this book was originally presented by the author as a thesis for the degree of Ph.D. to University College London. In this book two-hop and multi-hop D&F relay channels with half-duplex constraint on relays are studied. Channel's mutual information and outage probability are investigated for AWGN and Rayleigh fading channels. Optimum routing and optimum time allocation policies are also considered. In addition, a scheme is presented for user cooperation. Material offered in this book is useful to further investigate the visibility of relaying in wireless transmission and to develop user cooperative schemes. This book can be of use to communication and information theoretic researchers investigating relay channels, routing in wireless networks, cross-layer design, ad hoc networks, user cooperative communications and cognitive systems.